Lire Braudel : ouvrage collectif - Aymard, Maurice; Caillé, Alain; Dosse, François; Fourquet, François; Lacoste, Yves; Morineau, Michel; Steiner, Philippe; Wallerstein, Immanuel (Paris : La Découverte, 1988)
Bibliotheek François Vercammen
Frans
Monografie